‘DeltaCAN - A new data set of Canadian Arctic and subarctic coastal deltas’ - Mette Bendixen; Beatrice Roberge; Jenny Park; David Didier; Antoine Boisson; Haley Yorston; Lindsay Trottier; Ashley Hoblyn; Jackie Lee; Sadie MacDonald; Shan Zhao; Lauren Traboulsee; et al. (Scientific Data)
Abstract Arctic coasts constitute the critical interface between land and sea, and are subject to rapid changes caused by a warming climate. Current trends throughout the Arctic show increasing erosion trends, while other parts of the coast are experiencing prograding trends. Until now, a vast majority of our knowledge of Arctic coastal evolution is confined to site-specific studies with limited geospatial representation. Here, we present DeltaCAN, a novel data set on the locations of Canadian deltas larger than 500 m in width derived by visual interpretation of freely available satellite imagery. DeltaCAN is Canada’s first nationwide coastal detection covering 250.000 km of coastline in the Arctic, identifying 2712 deltas. The inventory is based on inspection of remotely-sensed satellite imageries, developed through an expert-based mapping approach where we implemented a quality control mechanism to assess the completeness of the data set. The DeltaCAN data set allows for assessing changes at an unprecedented spatial extent, improving our understanding of delta morphodynamics.